Model Health Literacy berbasis Telehealth dalam Promosi Kesehatan Mengenai Perilaku Makan pada Pertumbuhan Remaja Cegah Stunting - Melati Inayati Albayani; Marthilda Suprayitna; Zuhratul Hajri; Henny Yolanda (STIKes YARSI Pontianak, 2026)
Background: Nutrition and stunting issues in Indonesia cannot be underestimated, especially considering the health conditions of adolescents that influence stunting rates in the future. Adolescence is a crucial period in individual growth and development, where many behaviors and habits, including eating patterns, are formed. Good health literacy allows adolescents to understand health information related to nutrition and a healthy lifestyle. This shows that understanding and knowledge about balanced nutrition are crucial to reduce the risk of long-term stunting and ensure maternal and child health. The gap in knowledge and nutritional literacy among adolescents is a major challenge that needs to be addressed. A telehealth-based health literacy model is expected to improve understanding and healthy eating behavior among adolescents, as an automotive step in stunting prevention. Objective: The purpose of this study is to develop a telehealth-based Health Literacy model to improve healthy eating behavior among adolescents by focusing on strengthening their understanding of the importance of a healthy diet. Method: This study used the Research and Development method combined with a Randomized Control Trial. The sample in this study were adolescents attending high schools in Mataram City. Results: Statistical analysis showed a significant intervention effect with p<0.01. The proportion of improvement in the intervention group was more than double that in the control group. Conclusion: The Telehealth-based Health Literacy Model intervention was effective in improving adolescents' dietary knowledge and behavior.